Medical students’ professional identity formation during a social upheaval: a qualitative study - Mokhachane, Mantoa (University of the Witwatersrand, Johannesburg, 2023)
This phenomenological qualitative study, with an autoethnographic aspect, explored the University of the Witwatersrand’s medical students’ experiences of professionalism and professional identity formation amidst protests and social upheaval, namely, #FeesMustFall protests. The socio-historical autoethnographic sections emanate from my undergraduate journey in the same medical school 32 years before this study. I interviewed 13 participants. The participants’ stories echoed my own story during my undergraduate years in medical training, hence the inclusion of autoethnography. In this study, I question the under- representation of previously marginalised groups in the discourse of professionalism and professional identity formation. I also question the lack of an African influence on professionalism and professional identity formation. This study was conducted at the University of the Witwatersrand after obtaining Human Research Ethics Committee approval. I used an interpretive qualitative phenomenological enquiry in order to understand the meaning of students’ experiences. I also did not want to bracket myself, as my experiences resonated with those of the contemporary students, hence the choice of an interpretive instead of a descriptive phenomenological approach. A purposive sample was drawn from medical students. Thirteen semi-structured interviews were conducted in 2020, during the Covid-19 pandemic. Interviews were conducted with 13 participants, eight final-year medical students and five recent graduates who were in the first- or second-year internship (residency) training. The participants were five women (four Black and one White) and eight men (five Black and three White). An interview guide was used to probe the students’ journeys towards becoming doctors, their experiences during the #FeesMustall protests, experiences of professionalism and how #FeesMustFall impacted their professional identity development. Interviews were transcribed verbatim and analysed in MAXQDA 2020. I used an inductive approach, where each transcript was analysed as an individual case for the essence of its meaning and how participants’ experiences influenced their being and becoming doctors. When analysing the data through an African lens, Ubuntu, I used metaphors to allow the reorientation of professional identity formation, what professionalism means to contemporary students and how professionalism is weaponised against those who do not fit the western ideals of a medical professional. Racism was the foundation of many ills in medical education, particularly in the clinical spaces at the hospitals affiliated with the University of the Witwatersrand. This study highlights the contribution of Ubuntu-based values on professional identity formation and the influence of Ubuntu on the meaning of professionalism to contemporary medical students and recent graduates. It adds an African voice to the global western professional identity theories. This study encourages other researchers to explore their contexts to define professionalism and how professional identity is attained. I recommend reconstructing professionalism using Ubuntu as professionalism in medical education through letsema, Ubuntu, advocacy, and the acceptance of the intersectionality with which trainees enter medical education
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg 2023
Keywords: African influence on professional identity formation; Ubuntu as professionalism; Professionalism; Professional identity formation; Ubuntu; Lebollo; Letsema; Weaponisation; UCTD; SDG-3: Good health and well-being